My finest work yet [compact disc] - Bird, Andrew, 1973- (Loma Vista Recordings, 2019)
Andrew Bird grapples with themes of current day dichotomies and how to identify a moral compass amidst such diverse times. He tackles these topics with a more direct songwriting approach than his previous releases.